Evaluate the Results of Closed Interlocking Nail Shaft of Femur Vs. Open Interlocking Nail - Shams Ur Rehman, Syed Bakht Sardar, Kamran Saeed, Raza Askari, Fazl Ur Rahman Saeed, Irfan Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research is to evaluate the efficacy of closed versus open interlocking nails in treating femur shaft fractures. Study Design: Retrospective cohort study Place and Duration: This Retrospective cohort study was conducted at MTI Lady Reading Hospital Peshawar and Khyber Teaching Hospital Peshawar in the duration from 1st March, 2022 to 31 August, 2022. Methods: This research involved 108 cases with age 20-72-year had femoral shaft fracture were included. After informed written consent, age, sex, body mass index, and fracture reason were computed. Patients were equally divided in two groups. Group I utilized open interlocking nails, whereas group II used closed. Post-operative radiological and surgical results were evaluated for union, non-union, and delayed union. Calculated infection prevalence for both groups. Flynn's criterion assessed functional results. SPSS 24.0 analyzed all data. Results: In group I operation time was higher as compared to group II with p value <0.004. Closed group union time was 17.3±6.51 weeks compared to open group 27.8±6.20 weeks. Group II had 51 (94.4%) unions, whereas group I had 45 (83.3%). Group I had 12 (22.2%) delayed unions while group II had 5 (9.3%). Closed interlocking nail performed better than open approach with p value <0.03. The closed interlocking group had fewer complications as compared to open approach (p <0.02). Conclusion: This study found that closed interlocking nails for the femur shaft were superior to open interlocking nails in terms of radiographic and functional success. In addition, patients who were given a closed interlocking nail experienced less complications after surgery. Keywords: Surgery, Femur Shaft, Complications, Closed/Open interlocking nail, Functional Outcomes